SUBSTITUSI SEBAGIAN PUPUK ANORGANIK DENGAN PUPUK HAYATI TERHADAP PRODUKSI BAWANG MERAH - Arief Widyantoro; Anandeya Satrio Sambodo; Sariman Karta Rahayu; Supriyanto Supriyanto (ZIRAA'AH MAJALAH ILMIAH PERTANIAN, 2024)
Shallots are an important crop with high economic value in Indonesia. Shallot production usually depends on intensive fertilization. Inorganic fertilizers were increasingly rare and more expensive at the market level. Inorganic fertilizers were scarce in society and their prices were more expensive at the market level. Biofertilizers made from superior microbial active ingredients have long been used to substitute inorganic fertilizers, but the right combination dose has not been found to increase the yields. The research aimed to study the level of effectiveness of biological fertilizers in substituting inorganic fertilizers and getting the right dose to increase shallot production. The research was conducted from February to April 2019 in the Research Plantation of PT. Indo Acidatama Tbk, Karanganyar, Central Java. Four treatments were tested on shallot seeds under a completely randomized design non-factorial: (P1) NPK 1200 kg/ha, (P2) NPK 900 kg/ha + biofertilizer 10 l/ha, (P3) NPK 600 kg/ha + biofertilizer 20 l/ha, dan (P4) NPK 300 kg/ha + biofertilizer 30 l/ha. The results showed that 20 l/ha of biofertilizers combined with a dose of 600 kg/ha of inorganic fertilizer effectively increases shallot production to reach 6.78 tonnes/ha. Biofertilizers could substitute several inorganic fertilizers so that are indicated by optimally wet biomass weight, weight of bulbs, number of bulbs, and diameter of bulbs.